The security dilemma in Russia’s new national security strategy: between militarism and being a geographical pivot - Fernandes, Sandra (2022)
The article analyses the new Russian Security Strategy as a formulation of Russia's “security dilemma”, both in terms of interpretation and response (Booth and Wheeler 2007). Very focused on the transformation of the world order, resulting from changes in the International System, within which the powers seek to strengthen their positions in the global structure, the strategy increasingly foresees the use of the military instrument as a way of guaranteeing and imposing national interests, which are reflected in different domains and regional areas. Exploring the strategic relations with China, in economic and political terms, Russia also seeks to strengthen its status as a global power, through the expansion of geographic space and areas of intervention. In its interpretation of the so-called “modern world”, very marked by the rivalry between the US and China, it seeks to assume itself as the geographical pivot of that same relationship. The National Security Strategy therefore is a roadmap for Russia's ambitions, assessing the motives, intentions and capabilities of the "others" and identifying the "rational" and "legitimate" ways of responding to its "security dilemma". Whereas it is possible to confirm that the invasion of Ukraine on 24 February 2022 materialized the elements present in the strategy, the effects do not seem to coincide with the objectives sought by Moscow.